Endothelial Targeted Strategies to Combat Oxidative Stress: Improving Outcomes in Traumatic Brain Injury - Lutton, Evan M.; Farney, S. Katie; Andrews, Allison M.; Shuvaev, Vladimir V.; Chuang, Gwo-Yu; Muzykantov, Vladimir R.; Ramirez, Servio H. (Frontiers in Neurology, 2019)
The endothelium is a thin monolayer of specialized cells that lines the luminal wall of blood vessels and constitutes the critical innermost portion of the physical barrier between the blood and the brain termed the blood-brain barrier (BBB). Aberrant changes in the endothelium occur in many neuropathological states, including those with high morbidity and mortality that lack targeted therapeutic interventions, such as traumatic brain injury (TBI). Utilizing ligands of surface determinants expressed on brain endothelium to target and combat injury mechanisms at damaged endothelium offers a new approach to the study of TBI and new avenues for clinical advancement. Many factors influence the targets that are expressed on endothelium. Therefore, the optimization of binding sites and ideal design features of nanocarriers are controllable factors that permit the engineering of nanotherapeutic agents with applicability that is specific to a known disease state. Following TBI, damaged endothelial cells upregulate cell adhesion molecules, including ICAM-1, and are key sites of reactive oxygen species (ROS) generation, including hydrogen peroxide. Reactive oxygen species along with pro-inflammatory mediators are known to contribute to endothelial damage and loss of BBB integrity. The use of targeted endothelial nanomedicine, with conjugates of the antioxidant enzyme catalase linked to anti-ICAM-1 antibodies, has recently been demonstrated to minimize oxidative stress at the BBB and reduce neuropathological outcomes following TBI. Here, we discuss targeted endothelial nanomedicine and its potential to provide benefits in TBI outcomes and future directions of this approach.